'Giving birth to my breath': an an exploration of self-revelatory performance in facilitating a process of confronting and transforming a negative self-concept of afrikaner identity = 'Ek gee geboorte aan my asem': die gebruik van self-onthullingsteater om die negatiewe self-begrip van afrikaneridentiteit te konfronteer en transformeer - Meiring, Leané (My University, 2017)
This multi-lingual autobiographical performance-as-research (PAR) project critically analyses self-revelatory performance as a drama therapy method that can be used to effectively mitigate the lingering effects of a negative self-concept of Afrikaner identity brought on by the collective trauma of our past in South Africa. The research enquires and demonstrates; in what ways the method of self-revelatory performance is effective in mitigating the effects of collective trauma both on intra-psychic and interpersonal levels through the lived experience of the researcher, training drama therapist and client-performer who underwent a process of devising, scripting, rehearsing, and performing a piece of autobiographical theatre in front of an invited audience. The methodology is firmly located within, and founded on the core principles of art-based research and more specifically, PAR; this choice of method of enquiry is as a result of the performative and embodied nature of the method of self-revelatory performance. The findings of the research are a collaborative process of practice (performance), self-reflexivity and theory working together to answer the research question. The research demonstrates the need for performative methods of drama therapy, such as self-revelatory performance, to be explored within our South African context. The research illuminated the need to adapt the methodology when working with collective trauma in our South African context and the need to clearly define the role of the audience, and the conditions of collective witnessing that determine psychological safety and containment, in the method of self-revelatory performance within our socio-cultural context.
A Multi-Lingual Performance-as-research project submitted in fulfilment of the requirements for the Master of Arts in Drama Therapy at Drama for Life, A division of the Wits School of Arts Faculty of Humanities, University of the Witwatersrand, March 2017
Keywords: Drama--Therapeutic use--South Africa; Narrative therapy--South Africa; Psychotherapy--South Africa